Case report: Oropharyngeal injuries with GlideScope® usage in two obese patients. (2nd January 2016) - Curran, C
Abstract : The GlideScope® is a widely used video laryngoscope that is especially beneficial in the setting of the anticipated difficult airway. However, its design introduces blind spots and necessitates the need for a curved stylet, most commonly the accompanying GlideRite® Rigid Stylet. A combination of these features and incorrect technique has resulted in cases of oropharyngeal injury, especially to the tonsillar pillars. Two cases of oropharyngeal injury are presented that were sustained during the use of the GlideScope® in the East London Hospital Complex. Both patients were obese. The recommendations presented in the literature to avoid such injuries are also summarised.